PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN TALKING STICK DENGAN MODEL PEMBELAJARAN TALKING CHIPS PADA MATA PELAJARAN IPS SISWA KELAS V GUGUS III KECAMATAN SITUBONDO TAHUN PELAJARAN 2017/2018 - Dodik Eko Yulianto (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2018)
Student learning is expected to obtain and find the value of quality science that is delivered by the teacher, therefore the teacher in presenting the lesson needs to be directed to the fulfillment of the needs and expectations of the students by using various sources of information. But to create an atmosphere of learning like that is not an easy matter. Other components are needed to support the learning process so that it is easy and enjoyable. In this case the researcher is interested to conduct research on the difference of Student Learning Results Using Learning Talking Model Stick with Learning Model Talking Chips on Subject Ips Students Class V Gugus III Situbondo Sub-District Situbondo District Lesson Year 2017/2018. This research was carried out in Cluster III Class V as many as 55 students consisting of 30 grade V students (SD Negeri 5 Dawuhan) using the Talking Stik learning model and 25 fifth grade students (SD Negeri 3 Dawuhan) using the Talking Chips learning model. This type of research is quantitative research and the research method is quasi-experimental. The data obtained were collected using test methods, observation, interviews, and documentation. While the data analysis used is Normality Test, Homogeneity Test and Hypothesis Test. Based on the results of statistical tests data have been obtained that is Thitung> T table with Thitung = 5,043 and T table = 1.674 at significance level α (0,05) this shows that application of learning model Talking Stik was more effective and significant compared with using model of learning Talking Chips although using the same Basic Competency and Competency Standards as learning resources and media